Paradigmenwechsel als Feld strukturellen Lernens Konsequenzen für die Herausbildung von Lernkulturen in der Transformationsgesellschaft - Hilliger, Birgit (Verlag Barbara Budrich, 2012)
Social changes create challenges. How can adult education meet these challenges? How do learning processes in companies change in the face of constant social transformation? Which learning cultures are sustainable? Birgit Hilliger pursues these complex questions in a highly informed manner and makes a valuable contribution to a learning theory based on social theory.